Treatment Outcome of Tuberculosis Cases and HIV Co-infected Patients. A Retrospective Study at a Federal Medical Centre of North Central Nigeria - Thaddues Okonkwo Eze; Finian Chimezie Nwadinigwe; Gabriel Mathias Ameh (Jurnal Epidemiologi Kesehatan Komunitas, 2023)
Background: Tuberculosis (TB) is the leading cause of death among people living with HIV/AIDS worldwide. Despite the availability of highly effective treatment for decades, Tuberculosis (TB) remains a major health problem in Nigeria due to the increasing association between HIV and TB observed over the past three decades when HIV was discovered. However, the proportion of TB and or TB/HIV co-infected patients who have successful TB treatment outcome is not well known. This study determined the treatment outcome of TB/HIV co-infected patients with HIV negative patients at Federal Medical Centre Makurdi, Benue State, Nigeria. Methods: A retrospective study that used secondary data from Directly Observed Treatment Short (DOTS) course center (APIN Unit). 268 cases were considered and the period under review covers from January, 2019 to December, 2021. Results: Out of the total 268 TB cases reviewed, the HIV prevalence rate was 28.7 %. More than two-third (78.4%) of HIV-negative patients had successful treatment compared to 68.9% of HIV positive patients that were treated successful.  Out of the 77 HIV co-infected patients, 10.4% defaulted, 14.2% had died, and 6.5% failed treatment compared to HIV-negative patients amongst whom 15.2% defaulted, 4.8% died and 1.6% failed treatment. TB/HIV co-infection was significantly associated with poor treatment outcome (AOR: 1.158; 95 % CI 0.617-2.173; p = 0.648).Conclusion: The favorable treatment outcome of HIV-negative patients is more than that of HIV-positive patients and the most probable predictable factor responsible is the CD4 count of patient; indicating that TB/HIV co-infection has remained a major public health problem in Benue state. Therefore, there is the need for sustained strengthening and expansion of the national TB/HIV programmes.